Investigating the Factors Contributing to Low Mathematics Performance in Tanzanian Ordinary Secondary Schools - Deogratias, Emmanuel; Paulo, Heri (International Journal of Research in Mathematics Education, 2025)
This quantitative study aimed to investigate the factors contributing to low mathematics performance in secondary schools within Morogoro Municipality, Tanzania.. Relevant literatures reviewed on findings that emerged from different authors. The study involved in 3 secondary schools, 50 mathematics teachers and 150 students. These helped us to obtain numerical data through simple random sampling Data collection conducted by using questionnaires, then the data were analyzed using statistical package software (SPSS). It was found that teacher lack of professional training contribute to low performance in mathematics, inappropriate teaching methods effect on student’s performance in mathematics, class size contribute to low performance in mathematics,, teaching materials and use of ICT contribute to high performance in mathematics, appropriate using teaching and learning resources in teaching Mathematics contribute to high performance, parental educational status contributes to low performance in mathematics, students’ attitude towards mathematics contribute to low performance in mathematics, the teacher- student- relationship contribute positively or negatively towards low performance in mathematics subject, and classroom and school environment contribute either positively or negatively towards low performance in mathematics. These results have implication in improving performance in mathematics for students in secondary schools.